Determining a critical threshold for G6PD activity below which red blood cell response to oxidative stress is poor - Swastika, Maria (Malar J, 2020)
BACKGROUND: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzyme disorder in the world. Its main function is to generate NADPH that is required for anti-oxidative pathway in the cells especially in red blood cells (RBC). G6PD deficiency is X-linked and thus subject to random X-chromosome inactivation in women giving them mosaic expression of G6PD activities in their individual cells. This phenomenon makes it difficult for diagnosis with the currently available G6PD qualitative diagnostic tests. With the rolling out of newly marketed anti-malarial drug tafenoquine, which has a long half-life, screening for G6PD deficiency becomes a necessity where those with < 70% G6PD activity cannot receive this drug. Thus, evidence for a quantitative cut-off for G6PD activity is needed to ensure safe drug administration. METHODS: RBC models were developed to analyse the effect of oxidant on RBC oxidative markers namely total glutathione (GSH)and malondialdehyde (MDA). G6PD activity was measured using quantitative assay from Trinity Biotech and was correlated with cytofluorometric assay. RBC from two G6PD heterozygous women with different G6PD activities were also analysed for comparison. RESULTS: There was a negative correlation between G6PD activity and CuCl concentration and a strong association between G6PD activities and proportion of G6PD normal RBC in CuCl-treated models and in ex vivo RBC. However, in terms of oxidative stress markers analyses, unlike the hypothesis where the lower G6PD activity, the higher MDA and the lower GSH level, the CuCl RBC model showed that in low G6PD activities (10–30%) cells, the MDA level is lower compared to the rest of the models (p < 0.05). The ex vivo models however were in line with the hypothesis, although the result was not significant (p = 0.5). There was a significant difference between RBC with < 60% and those with > 80% G6PD activities in CuCl RBC model, but not in ex vivo RBC (p = 0.5). Genotyping heterozygous subjects showed G6PDViangchan variant with 2.97 U/gHb (33% activity) and 6.58 U/gHb (74% activity). CONCLUSIONS: The GSH analysis has pointed to the 60% G6PD activity cut-off and this data is supportive of the old World Health Organization threshold for intermediate upper limit of 60% G6PD activity. However, there are significant limitations in using MDA assay with CuCl RBC model because the RBC was already stressed due to the copper treatment and thus present a different result when compared to the ex vivo model.